O ensino de língua portuguesa a partir das necessidades e expectativas de alunos de EJA - Santos, Manoel Josiano dos (2012)
The aim of this research is to show some reflexion resulting from textual production work which has been done in classroom with EJA students (Young Adult Education) and describe the results from a development teaching purpose regarding the needs and objectives of students who were involved in this research. This work was based upon Proposta Curricular para a Educação de Jovens e Adultos (BRASIl, 2002a); Diretrizes Curriculares para a Educação de Jovens e Adultos (BRASIL, 2000a and BRASIL, 2000b). The studies about social representation of Gilly (2001) and Harré (2001) are also very important to this work, as well as the studies about textual production based on Marcuschi (2007a e 2007b), Bazerman (2009) and Widdowson (1991). The context of the research was a public school in São Paulo state, which we observed for one semester an evening group of High School in the 1st. term. The material used for comprehension was collected from the activities developed in class along the second semester in 2011. The results of this research show that EJA students present some peculiarities regarding the development of textual production skills. Many students don t reveal the desire of developing texts commonly worked in Portuguese language teaching in high school, such as write dissertations, showing that there is a need to work with a variety of pedagogical purposes that consider the needs of different target public. These results allow us to have an idea that is not necessary a specific teaching program to Young Adult Education, but to work with some flexible purpose taking into consideration the specific target public